DYT-6 DYSTONIA WITH DRUG INDUCED CHOREA AND AN EXCELLENT RESPONSE TO GPI DEEP BRAIN STIMULATION - ZH. MYRZAYEV; CH. SHASHKIN; D. BAGAUTDINOV; H. HOULDEN; R. KAIYRZHANOV (Avicenna Tajik State Medical University, 2022)
Dystonia-6 (DYT-THAP1, DYT6) is an autosomal dominant movement disorder characterized by early involvement of craniofacial muscles with secondary generalization. DYT6 is caused by heterozygous variants in the THAP domain-containing protein 1 (THAP1) gene. Currently, more than 90 different pathogenic missense and truncating THAP1 variants have been reported - mainly in people from Europe but also from China and Brazil. However, no cases of genetically confirmed DYT6 have been described in Central Asian countries. Here the first case of genetically confirmed DYT6-dystonia from Central Asia is described. The proband had adolescent-onset focal dystonia with secondary generalization, trihexyphenidyl induced persistent chorea and robust and sustained response to globus pallidus internus deep brain stimulation. Her definitive diagnosis has been made 39 years after the onset of the disease keeping her for almost 4 decades disabled. This paper highlights the urgent need for movement disorders specialists in Central Asia as well as access to free genetic testing and deep brain stimulation surgery.